INCIDENCIA DE LOS ESTUDIOS DE POSTGRADO EN DOCENCIA EN EL DESARROLLO ACADEMICO DE LA FACULTAD DE CIENCIA DE LA EDUCACION DE LA UNIVERSIDAD TECNICA DE BABAHOYO, LINEAMIENTOS ALTERNATIVOS. - AIDA CASTRO POSLIGUA (2005)
IMPACT OF POSTGRADUATE STUDIES IN TEACHING ON THE ACADEMIC DEVELOPMENT OF THE FACULTY OF EDUCATIONAL SCIENCE OF THE TECHNICAL UNIVERSITY OF BABAHOYO, ALTERNATIVE GUIDELINES.